(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: During endoscopic examination of the upper gastro-intestinal tract, some endoscopic changes in the duodenal mucosa may suggest Celiac disease. Patients and method: We studied 102 patients, referred to the endoscopy unit for evaluation of the possibility of Celiac disease. All patients underwent upper gastrointestinal endoscopy and biopsy specimens were taken from the descending duodenum and sent for histopathological study. Results: The main symptoms of patients were short stature and chronic diarrhea. Atrophic duodenal mucosal folds and scalloping of the valulae conniventes were found in 31 of 34 patients with subtotal villous atrophy. The sensitivity and specificity of this result were 91 percent and 75 percent respectively. Conclusion: For early diagnosis of celiac disease biopsy study of the duodenal mucosa should be done in all patients when there are endoscopic changes in the duodenal mucosa like atrophic mucosal folds and presence of scalloping of the valvulae conniventes. Key words: Celiac Disease, Endoscopy, Histological Changes Iraqi J Med Sci, 2004; Vol. 3 (1): 51-54